2009
DOI: 10.1152/ajprenal.90652.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of BSA-induced ER stress on SGLT protein expression levels and α-MG uptake in renal proximal tubule cells

Abstract: Recent studies demonstrated that endoplasmic reticulum (ER) stress regulates glucose homeostasis and that ER stress preconditioning which induces an adaptive, protective unfolded protein response (UPR) offers cytoprotection against nephrotoxins. Thus the aim of the present study was to use renal proximal tubule cells (PTCs) to further elucidate the link between the BSA-induced ER stress and alpha-methyl-d-glucopyranoside (alpha-MG) uptake and to identify related signaling pathways. Among ER stress inducers suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 61 publications
(61 reference statements)
5
32
0
1
Order By: Relevance
“…A slight activation of NF-B was observed in control groups. It has been reported that serum albumin activates NF-B in RPTCs (18). Therefore, the minor activation of NF-B in the control groups might have been caused by the replacement of medium containing 1% FBS, which was required to prevent the loss of RPTCs character Fig.…”
Section: Discussionmentioning
confidence: 96%
“…A slight activation of NF-B was observed in control groups. It has been reported that serum albumin activates NF-B in RPTCs (18). Therefore, the minor activation of NF-B in the control groups might have been caused by the replacement of medium containing 1% FBS, which was required to prevent the loss of RPTCs character Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Urinary albumin is also known to cause ER stress in tubular epithelial cells [2,4,5]. However, signaling pathways have not been revealed completely.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of 15D-PGJ 2 have been shown not only in the liver, but also in the lung (11), kidney (23), and other organs. Therefore, with a peritoneal injection of 15D-PGJ 2 , it is uncertain whether this agent directly exerts beneficial effect on the liver or via a systemic effect.…”
Section: Discussionmentioning
confidence: 99%